Unemployment in Bolivia: Risks and Labor Market Policies - Werner Hernani; Maria Villegas; Ernesto Yanez (Inter-American Development Bank (IDB), 2011)
This paper attempts to evaluate the effectiveness of Bolivias labor market institutions, particularly the Plan Nacional de Empleo de Emergencia (PLANE). It is found that unemployment as conventionally defined may not be the most important problem in Bolivias labor market, as the non-salaried market is always an alternative. While un- employment durations and unemployment scarring consequences are relatively low, labor market regulations and labor market programs do not help to increase the size of the formal market, apparently as a result of Bolivias rigid labor markets and labor policies based mainly on temporary employment programs. Such programs, however, may have helped to smooth consumption. Given the countrys high level of infor- mality, protection policies are second best to active policies specifically designed to increase the productivity/employability of vulnerable populations.
Keywords: J08; J21; J64; 330